Effect of Anthelmintic Treatment on the Agreement Between Real-Time Polymerase Chain Reaction (RT-PCR) and Kato–Katz Microscopic Technique in the Diagnosis of Soil-Transmitted Helminth Infections - Paul Alvyn Nguema-Moure; Jean Claude Dejon-Agobé; Roméo-Aimé Laclong Lontchi; Gédéon Prince Manouana; Moustapha Nzamba Maloum; Brice Meulah; Danny Carrel Manfoumbi Mabicka; Marguerite Emmanuelle Nzame Ngome; Peter Gottfried Kremsner; Ayôla Akim Adegnika (Parasitologia)
Soil-transmitted helminths (STHs), including Ascaris lumbricoides, hookworm species, and Trichuris trichiura, cause significant morbidity worldwide. For an effective proper control of their morbidity, accurate diagnosis method is needed. To this end, a polymerase chain reaction (PCR) method has been developed, but its use remains limited due to the high cost of its implementation, the resources required, and the lack of qualified technicians. The objective of the present analysis is to assess the agreement between the Kato–Katz microscopy method and quantitative real-time PCR (RT-PCR) in the diagnostic of STHs before and after treatment, to decipher the usefulness of either technique for evaluation of the treatment. Methods: Stool samples were collected before and after three- or six-weeks post-treatment from study participants and analyzed using Kato–Katz and RT-PCR methods for the diagnosis of STHs infections. The cure rate (CR) was estimated according to each diagnostic method. Agreement between CRs was tested using the Kappa statistical test. Results: Agreement between Kato–Katz and RT-PCR methods varied regarding the STH species targeted and was different after treatment compared with before treatment. At baseline, the two diagnostic methods showed a moderate agreement (0.45 < K < 0.5) for all STH species, whereas after treatment, concordance decreased slightly (0.11 ≤ K ≤ 0.14) for A. lumbricoides, remained moderate (0.5 ≤ K ≤ 0.53) for T. trichiura, and went from moderate to absent for hookworms. Conclusion: Our findings showed basically a moderate agreement between the Kato–Katz method and RT-PCR. There is a likely association with a moderate proportion of microscopy-positive cases. Reciprocally, a decrease in agreement after treatment was observed with low microscopy-positive cases after treatment, whereby RT-PCR was more likely to detect positive cases than microscopy. Therefore, the agreement is positively associated with an increasing in the number of samples testing positive.